Initial experience with Tadalafil in Pediatric Pulmonary Arterial Hypertension - Takatsuki, Shinichi (2012)
Our objective was to investigate the safety, tolerability, and effects of tadalafil in children with pulmonary arterial hypertension after transition from sildenafil or receiving tadalafil as initial therapy. Thirty three pediatric patients with pulmonary arterial hypertension were retrospectively evaluated. Twenty nine of 33 patients were switched from sildenafil to tadalafil. The main reason for changing from sildenafil was once daily dosing. The average dose of sildenafil and tadalafil were 3.4+/−1.1 mg/kg/day and 1.0+/−0.4 mg/kg/day, respectively. In 14 of 29 patients undergoing repeat catheterization, statistically significant improvements were observed following transition from sildenafil to tadalafil, in mean pulmonary arterial pressure (mmHg) (53.2+/−18.3 versus 47.4+/−13.7, p<0.05) and pulmonary vascular resistance index (unitsxm(2)) (12.2+/−7.0 versus 10.6+/−7.2, p<0.05). In 4 patients treated with tadalafil as initial therapy, clinical improvement was noted. Side effect profiles were similar in patients who had transitioned from sildenafil to tadalafil and included headache, nausea, myalgia, nasal congestion, flushing, and allergic reaction. Two patients discontinued tadalafil due to migraine or an allergic reaction. One patient on sildenafil had no break through syncope after transition to tadalafil. Tadalafil can be safely used in pediatric patients with pulmonary arterial hypertension and may prevent disease progression.